(untitled) (Agricultural Engineering, 2017)
The paper presents the results of analysis which enable determination of the value of the pressure losses coefficients which occurred during air suction and flow through a perforated pipe. Knowledge on them is indispensable for determination of regularity of air suction along the considered pipe. Exiting the basic energy equation, firstly a local coefficient of pressure losses was determined and then the form of the relation for its determination in the function of independent variables was found out. In the second stage, the value of pressure losses caused by mutual crossing of two streams (axial stream and stream sucked by the side surface of a pipe) was determined. Also, for this coefficient, the form of the correlation equation including power relation between the independent variables was emphasised. The calculated values of the discussed coefficients from determined forms of correlation equations are satisfactorily compliant with the calculated values from the experiments which were carried out.